The Wire - The Complete Second Season Episode 1-12 - Bianchi, Edward; Keene, Elodie; Shill, Steve; Briesewitz, Uta; West, Dominic; Doman, John; Elba, Idris (Warner, 2005)
In chronicling a multi-generational family business dealing illegal drugs and the efforts of the Baltimore police to curb their trade, this series draws parallels between these organizations and the men and women on either side of the battle ... Season Two steps away from the drug trade (while still mentioning characters from the previous season) to a case of dead prostitutes which turns into a look at the corruption surrounding the Port. [www.tv.com]